Elaboration of GIS Based Multidisciplinary Data for Microzoning Studies - Papadopoulos, T. D.; Voulgaris, N. S.; Alexopoulos, J.D. (Environmental Semeiotics, 2009)
The elaboration of analytical microzoning studies involves a multidisciplinary approach comprising geological, geotechnical, seismological, geophysical and dynamic soil analysis data. In an attempt to incorporate the maximum available amount of information and in the view of the continuously expanding use of GIS, as a tool for analyzing and integrating data, a new software environment called AUTO-SEISMO-GEOTECH has been developed for handling these multi-parameter data. This user friendly package is presently implemented for the cities of Heraklion (Crete island- province of Heraklion) and Thiva (province of Viotia) in Greece. The pilot methodologies applied in these urban areas, aimed also at determining a minimum package of tasks/methods needed for the elaboration of a microzoning study, are described and evaluated here. Next, a database with appropriate architecture was formed in order to handle all available geo-information for each city separately and produce thematic maps, such as geological, tectonic, hydrogeological, seismic hazard and microzonation ones. These maps can be easily reproduced, integrated and used for building safer constructions contributing so to mitigation of earthquake consequences. Geo-information obtained by a) existing regional seismicity maps and installation of local portable seismographic networks around both cities, to monitor the microseismic activity and define possible active fault zones, b) geological mapping of the broader urban area in scale 1:5000, c) evaluation of existing geotechnical data as well as new data coming from boreholes, d) geophysical data resulting from surface and borehole techniques, for Vp, Vs and dynamic elastic parameters estimation and e) consideration of historical seismological data for seismic hazard estimation, have been incorporated in this GIS based platform, to be easily handled for further use. The output of this information combined with the dynamic soil analysis produces detailed microzonation maps. Such maps are valuable for city planners and urban designers.